Midwives’ perspectives regarding episiotomy practice in Kurdistan region/Iraq - Piro, Safiya Sabri; Ahmed, Hamdia Mirkhan (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Local professional norms, experiences in tainting, and individual provider preference may lead to wide practice variation in rate and practice of episiotomy by midwives. The aim of this study was to find out the midwives’ perspectives regarding practicing of episiotomy in three main cities of Kurdistan region/Iraq. Methods: A cross-sectional, descriptive study was conducted on 53 midwives working in delivery room in three maternity teaching hospitals in the three biggest cities of Kurdistan Region of Iraq. A questionnaire was constructed for the purpose of the study and data were collected by interview with midwives. F test and Chi-square test were used for analyzing the data. Results: The majority (88.7%) of midwives thought that the rate of episiotomy were high in their hospitals that were attributed to five factors; maternal (77.35%), fetal (39.62%), midwives (37.73%), obstetricians (30.18%) and hospital policy and health system (20.75%). The opinion of midwives regarding how to decrease the rate of episiotomy included improving midwifery care during delivery (77.35%), reforming health system (60.37%), reforming hospital policy (50.94%) and improving maternal care during pregnancy (26.41%). Conclusion: Taking into consideration the midwives’ perspectives and views regarding episiotomy and providing training courses may help in decreasing the rate of episiotomy and its practice in correct way in Kurdistan’s maternity hospitals.